RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDE OF ADOLESCENTS TOWARDS HIV/AIDS PREVENTION AT YPK IMMANUEL HIGH SCHOOL MANOKWARI - Mansa, Gidion; Ardiansyah, Fazrin; Nuryanti, Yayuk (NHM PRESS, 2024)
Global HIV Number In 2023, there will be 39.9 million people worldwide living with HIV. Of these, 38.6 million are adults and 1.4 million are children. Global HIV-related deaths. In 2023, 630,000 people will die from HIV-related causes worldwide. HIV cases in Indonesia. The estimate of PLHIV in West Papua Province in 2024 is 12,050 and PLHIV who have been found until January 2024 are 4,681 people or around 39%, still very far from the fast track target of 95%. To determine the relationship between knowledge and attitudes of adolescents towards HIV/AIDS prevention at SMU YPK Immanuel Manokwari 2024. This type of research is a quantitative research type with a quasi-experimental method or